PENANGGULANGAN PENYAKIT MASYARAKAT (MINUMAN KERAS) BERBASIS KEARIFAN LOKAL - Reffi Rahmadani; Noor Fadlli Marh (Journal of Innovative and Creativity, 2026)
The problem of alcohol consumption is one form of social illness that negatively affects social order and religious values in society. In Minangkabau society, niniak mamak play an important role as traditional leaders in guiding and supervising their clan members. This study aims to examine the role of niniak mamak in overcoming alcohol consumption in Jambak Jalur 1, Jambak Selatan, Luhak Nan Duo District, West Pasaman Regency, as well as the obstacles faced in carrying out this role. This research uses a qualitative approach with a descriptive method. Data were collected through in-depth interviews, observation, and documentation. The informants consisted of niniak mamak as key informants and community members as supporting informants. The results show that the role of niniak mamak is carried out through giving advice, direct warnings, moral guidance, and the application of customary sanctions in stages. However, in practice, several obstacles are still encountered, such as the declining authority of customary leaders, negative peer influence, and limited support from some community members. This study concludes that the role of niniak mamak remains relevant and necessary, but it needs to be strengthened through cooperation with religious leaders and the village government.